Nowe znaczenie posługi akolitatu? Urząd akolity w perspektywie rozwoju obrzędów święceń i ustanowień - Makowski, Dawid; Kwiatkowski, Emanuel (Warszawskie Studia Teologiczne, 2024)
The article presents the issue of the ministry of the acolyte in the aspect of the modification of the rites of conferring this ministry. The research question posed in the publication is whether the present form of the ministry of acolytes has a different meaning from that known before the post-conciliar liturgical reform. To this end, the publication identifies the development of the acolyte's ministry in the context of the ordination rites, with the first chapter dealing with the period from the fifth to the ninth century, the second chapter dealing with the rites of the second millennium up to 1961-1962, and the third chapter covering the post-conciliar rites of institution to the ministry of acolyte. This makes it possible to see how the image of the acolyte has changed over the centuries. The article uses a historical-analytical method, which makes it possible to see the different role of acolytes in the Church over the past centuries. At the same time, thanks to the dogmatic-pastoral perspective, the theological value of their ministry is made visible. In this way, the study undertaken answers not only the question: how was this ministry modified? but also: why was this done?